Quality of life among elderly asthmatic - ابراهيم غسان (Latakia University Journal -Medical Sciences Series, 2022)
Asthma is a chronic disease characterized by recurrent attacks ranging from shortness of breath and wheezing. Frequent asthma symptoms often cause insomnia and fatigue during the day and decreased activity levels and consequently a deterioration in the quality of life, especially in elderly patients, so this current study aimed to identify the level of quality of life in asthma patients The elderly among 50 elderly patients, who were selected using the convenient sample method. The data were collected using a questionnaire developed by the researcher himself, where the study showed that 58% of the participants have a good level of quality of life related to the physical dimension, and 60% of them have a good level of quality of life related to the dimension of mental health, and 68% of them have a good level of quality of life Life related to the dimension of social relations, and 56% of them had a good level of quality of life related to the dimension of environment, and in the field of the general level of quality of life, 64% of the participants had a good level of quality of life. The study recommended activating the participation of nursing, especially community health nursing and psychiatric nursing, in order to provide psychological and social support to elderly patients.